t/3+3=3

Simple and best practice solution for t/3+3=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t/3+3=3 equation:



t/3+3=3
We move all terms to the left:
t/3+3-(3)=0
We add all the numbers together, and all the variables
t/3=0
We multiply all the terms by the denominator
t=0

See similar equations:

| -12-13x=-233 | | x=85+(1/4x) | | -14-8a=-174 | | x=85+(x*0.25) | | 5(r+94)+-14=81 | | 14-10p=34 | | 8y-6(3y-7)=y | | 7-10a=-173 | | -11(6k-12)=0 | | 85=87-p | | 18x+15=-21+12x | | 9y=6y+33 | | -8(c-85)+32=-48 | | -8=7+5v | | -10(m-97)+-18=42 | | 3x+8=2x–17 | | v+3-6=-3 | | 2x+7=1.5√((x^2)+49) | | 4/7k-6/5=2-8/9k | | n+0.3n=91 | | 0.4(2x+0.3)=0.6666(6x−7.2) | | 13.1+10.3m+13.12=9m+9.06 | | 0.4(2x+0.3)=1 /3(6x−7.2) | | 5v=19+6v | | (w-4)^2-32=0 | | 3w-13=8 | | -14+20g=4+18g | | -9.65-11.9v=19.87-6.8v+2.1v | | s=4+0.75 | | -6x-14=5x-12 | | 6(9x-3)=78 | | -2z+20=18z |

Equations solver categories